2013
DOI: 10.1007/s00277-013-1692-6
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C in patients with β-thalassemia major. A single-centre experience

Abstract: Chronic hepatitis C (CHC) and iron overload are the main causes of liver disease in β-thalassemia major (βTM). There is limited data regarding the course of CHC in this population. All patients (n=144) from the thalassemia centre of the University Hospital of Patras were evaluated (January 1981 to June 2012). Patients were classified into group A (n=57), which consisted of patients with CHC, who either had received antiviral treatment (n=49) or not (n=8), and group B which included 87 patients without CHC. Nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 37 publications
4
13
0
Order By: Relevance
“…This datum is in accordance with previous studies from Greece25,26 and other European countries 27. As far as HCV genotype is concerned, almost half of our patients were infected with genotype 1b, which is the most prevalent genotype among multitransfused patients [3,28].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This datum is in accordance with previous studies from Greece25,26 and other European countries 27. As far as HCV genotype is concerned, almost half of our patients were infected with genotype 1b, which is the most prevalent genotype among multitransfused patients [3,28].…”
Section: Discussionsupporting
confidence: 94%
“…As far as HCV genotype is concerned, almost half of our patients were infected with genotype 1b, which is the most prevalent genotype among multitransfused patients [3,28]. In addition, nearly 20% of the patients had cirrhosis before treatment initiation which is in accordance with previous studies in patients with CHC and thalassemia,3,26,29 while the rate of progression of liver disease to cirrhosis was 27% with a median disease duration of 23 years. The progression to cirrhosis seems to be higher than that expected in other patients with CHC without haemoglobinopathies 30,31.…”
Section: Discussionsupporting
confidence: 87%
“…This raises serious concerns over the safety of blood products and reflects limitations of effective screening of blood donors. Our findings also confirm the results of previous studies that demonstrated lower pretransfusion hemoglobin levels among patients with splenomegaly, hepatomegaly, and hepatitis C infection 27,28. Similarly, we found that patients with hepatitis C infec-…”
supporting
confidence: 92%
“…The prevalence rates of hepatitis C virus (HCV) infection in adult patients with β‐thalassaemia major (β‐TM) have been reported to be high, although they vary widely among studies (Di Marco et al , ). Recent studies in Greece have shown prevalence rates ranging from about 40% to almost 75% (Kountouras et al , ; Triantos et al , ). In patients with β‐TM and chronic hepatitis C (CHC), the most prevalent HCV genotype is 1b, mirroring that of the general population in the same geographical areas (Di Marco et al , ).…”
mentioning
confidence: 99%